2014
DOI: 10.2298/sos1401055a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of porous clay ceramic using sago waste ash as a prospective additive material with controllable milling

Abstract: A novel type of ceramic material was produced by mixing sago waste ash from the sago processing industry in Indonesia with clay. The composition was prepared by adding 50 %wt amount of sago waste into the clay, then a series of samples was milled for 6 h, 12 h, 24 h and 48 h, respectively. The samples were dry pressed and sintered at temperatures ranging from 800?C to 1200?C. The influence of the sintering temperature and the milling time on bulk density, firing shrinkage, water adsorption, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…When the sintering temperature is 1000°C, the small pores are dominant in specimens A 0 and A 16. 5 and their average pore sizes (APZs) are 1.42μm and 1.73μm, respectively. With an increase of sintering temperature, the peak value of the small pore decreases, whereas, that of the large pore increases and the curve of PSD moves rightward.…”
Section: Pore Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sintering temperature is 1000°C, the small pores are dominant in specimens A 0 and A 16. 5 and their average pore sizes (APZs) are 1.42μm and 1.73μm, respectively. With an increase of sintering temperature, the peak value of the small pore decreases, whereas, that of the large pore increases and the curve of PSD moves rightward.…”
Section: Pore Characteristicsmentioning
confidence: 99%
“…Porous spinel ceramics can be prepared through an extrusion molding method, a foaming technique and a template method, etc. [2][3][4][5] However, the porous periclase-spinel ceramics prepared through the mentioned methods were not suitable as the lightweight refractory aggregates because of their large pore size, complex production processing and high cost. In-situ decomposition pore-forming (ISDP) technique is an alternative and environmentally friendly method to prepare the lightweight aggregates, which could utilize the decomposition of raw materials to create micro-sized pores [6].…”
Section: Introductionmentioning
confidence: 99%
“…Then the volume shrinkage ratio and bulk density of ceramic tile decrease slightly above 1200 ºC. This is related to the volume expansion of closed pores in the ceramic tiles due to the improvement of gases pressure inside the closed pores (Aripin et al, 2014). Moreover, a higher water absorption value shows higher apparent porosity of the ceramic tiles (Baccour et al, 2009;Martín-Márquez et al, 2008).…”
Section: Physical Properties Of Ceramic Tiles At Various Sintering Comentioning
confidence: 97%
“…Likewise, heterogeneity of sintered green body is result of preparation sample; size of raw materials, mixing, casting pressure and molding step. Diverse authors [3,19] had reported that milling time affects the microstructure homogeneity and reproducibility of the process. Besides J.H.…”
Section: Microstructure Of Green Bodiesmentioning
confidence: 99%
“…Porous ceramics have a wide range of applications, ranging from filtrations membranes and catalyst supports to biomaterials, thermally or acoustically insulating bulk materials or coating layers [1][2]. Well-controlled microstructures of porous size and pore distribution permit various applications [3]. These porous ceramics can be categorized in terms of their porous microstructures as: 3D-type with three-dimensionally connected and distributed open pores, 2D-type with slit-shaped open pores and 1D-type with unidirectionally oriented pores.…”
Section: Introductionmentioning
confidence: 99%